Folate receptor‐targeted 19F MR molecular imaging and proliferation evaluation of lung cancer. Issue 6 (13th May 2018) - Xu, Xiuan; Yan, Yuling; Liu, Fang; Wu, Lina; Shao, Mengping; Wang, Kai; Sun, Xilin; Li, Yingbo; Beinpuo, Ernest Sanyare Warmann; Shen, Baozhong
Abstract : Background: Folate receptors (FRs) hold great potential as important diagnostic and prognostic biological marker for cancer. Purpose: To assess the targeted capability of the FR‐targeted perfluorocarbon (PFC) nanoparticles and to assess in vivo the relationship between FR expression and tumor proliferation with fluorine‐19 ( 19 F) MR molecular imaging. Study Type: Prospective animal cancer model. Animal Model: H460 ( n  = 14) and A549 ( n  = 14) nude mice subcutaneous tumor models. Field Strength: 9.4T, 1 H and 19 F RARE sequences. Assessment: Intracellular uptake of the PFC nanoparticles was tested in H460 and A549 cell lines. 19 F MRI of H460 and A549 subcutaneous tumors was performed following intravenous injection of PFC nanoparticles. The concentration of PFC in tumors were compared. 3′‐Deoxy‐3′‐ 18 F‐fluorothymidine ( 18 F‐FLT) positron emission tomography / computed tomography (PET/CT) imaging, Ki‐67, and proliferating cell nuclear antigen (PCNA) staining were performed to confirm tumor proliferation. Statistical Tests: One‐way or two‐way analysis of variance. P  < 0.05 was considered a significant difference. Results: The diameter of the FR‐targeted nanoparticles was 108.8 ± 0.56 nm, and the zeta potential was –58.4 ± 10.8 mV. H460 cells incubated with FR‐targeted nanoparticles showed ∼59.87 ± 3.91% nanoparticles‐labeled, which is significantly higher than the other groups ( P  < 0.001). The PFC concentration in H460 tumors after injection with FR‐targeted nanoparticles was 4.64 ± 1.21, 8.04 ± 1.38, and 9.16 ± 2.56 mmol/L at 8 hours, 24 hours, and 48 hours, respectively ( P  < 0.05 compared to others). The ratio of 18 F‐FLT uptake for H460 and A549 tumors was 3.32 ± 0.17 and 1.48 ± 0.09 ( P  < 0.05), and there was more Ki‐67 and PCNA in H460 tumor than A549. Data Conclusion: 19 F MRI with FR‐targeted PFC nanoparticles can be used in differentiating of FR‐positive and FR‐negative tumors, and further, in evaluation of the two cancer models proliferation. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;48:1617–1625